Climato-geographical environment and the body mass of a newborn - О. М. Yuldasheva; L. A. Alexina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The body weight of 4131 new born boys and girls was studied in four regions of Kirgizstan. The body weight of a newborn was found to be inversely proportional to the altitude of the child residence: the higher was the altitude, the less was the body weight.